Retrospective Evaluation of Patients Admitted to the Pediatric Emergency Department with Intoxication - Alaaddin Yorulmaz; Hikmet Akbulut; İbaa Yahya; Raşit Aktaş; Halil Haldun Emiroğlu; Harun Peru (Galenos Yayinevi, 2017)
Introduction: In this study, we aimed to retrospectively analyze the demographic and epidemiologic features, clinical course, laboratory results and prognoses of the patients admitted to the department of pediatric emergency due to poisoning. Methods: This trial enrolled a total of 430 patients aged 1 month to 18 years. The medical data of the patients were reviewed retrospectively according to patient's medical record. Demographic data such as age, sex, time of occurrence, time of patient presentation to the emergency department, time to first medical intervention after taking the drug, cause of poisoning, received active substances, ways of taking, number of active substances received, and symptoms at admission to the hospital were analyzed. Results: The study population consisted of 0.74% of all patients who were admitted to the department of pediatric emergency. 243 (56.5%) patients were female and 187 (43.5%) were male. The age of the patients ranged from 4 months to 220 months (72.89±66.38). One hundred-thirteen (26.3%) of our patients were referred to our hospital in the summer, 111 (25.8%) in the spring, 110 (25.6%) in the autumn and 96 (22.3%) in the winter. Eighteen patients were admitted to our emergency department with poisoning in 2014, 193 in 2015, 178 in 2016 and 41 in 2017. 12.3% of our patients were referred to our emergency department between hours 00:00 and 08:00, 35.1% between 08:00 and 16:00 and 52.6% between 16:00 and 24:00. Ninety-six of the patients were admitted to our emergency department due to suicidal poisoning and 334 due to accidental poisoning. Nausea was present at the time of presentation in 142 (33.02%) of our patients, vomiting in 122 (28.37%) and dizziness in 102 (23.72%). Conclusion: We believe that determination of the epidemiological features of the poisonings in our country by large scale studies and public consciousness will contribute significantly to the prevention of childhood poisoning.